Selective Memory and the Legacy of Archaeological Figures in Contemporary Athens: The Case of Heinrich Schliemann and Panagiotis Stamatakis - Antoniadis, Vyron; Kouremenos, Anna (The Historical Review/La Revue Historique, 2021)
The legacy of antiquity has loomed large over the Greek capital since the foundation of the modern Greek state. Archaeologists have served as the main catalysts in the country’s endeavour to connect antiquity and modernity. Thus, the legacy of deceased archaeologists is tangible in many parts of Athens and a reminder of the significance of archaeology as a discipline in modern Greece. This article examines how the memory of Heinrich Schliemann and Panagiotis Stamatakis has been appropriated (or misappropriated) in the Greek capital. They worked together to bring to light treasures from Mycenae (1876) but shared a contemptuous relationship for the remainder of their lives. We aim to understand how society and the state treated not only the mortal remains of these two individuals but also their legacies. Hence, the abundance or absence of material evidence in Athens related to the maintenance of their memory will reveal how the archaeologists themselves worked to preserve or erase their posthumous legacy and how this has been appropriated.